Manajemen Sarana dan Prasarana di Sekolah Dasar: Penelitian - Rizqa Qodriannisa Hapsari; Choirun Nisa; Farid Cahyo Wibowo; Hanif Ar-Rif’an; Muhammad Misbahqul Umam; Hakim Nur Seha (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Optimal facility and infrastructure management is key to creating a learning environment that supports student achievement, yet various obstacles remain. This study aims to determine the implementation of facility and infrastructure management at SD Negeri 1 Nepen, including planning, organizing, maintaining, disposing of, and inventorying. Using a qualitative descriptive approach, data were collected through interviews, observations, and document analysis. The results indicate that facility management is quite effective, but is hampered by limited funding and a lack of administrative staff training. Recommendations include improving staff training, community involvement, and flexible budgeting for urgent needs. The study also suggests the use of a technology-based management model to improve the efficiency and accuracy of school facility management. This study contributes to understanding the challenges and practical solutions for managing school infrastructure with limited resources.